Meningkatkan Readiness for Change pada Karyawan: Peran Resiliensi, Kepemimpinan Transformasional, dan Modal Psikologis - Badruz Zaman, Ikhsan (Jurnal Locus Penelitian dan Pengabdian, 2025)
Organizational change is an inevitable challenge in the workplace. Employees’ readiness for change plays a crucial role in determining the success of organizational adaptation. This study aims to review the relationship between employee resilience and readiness for change. A literature review was conducted by analyzing 50 international academic journal articles published in the last ten years, sourced from databases such as Scopus, Web of Science, Google Scholar, and ScienceDirect. The data were analyzed using thematic synthesis to identify patterns and key findings from relevant literature. The results indicate that resilience significantly contributes to enhancing employees’ readiness for change, especially when supported by transformational leadership, a flexible organizational culture, and strong psychological capital. These findings underscore the importance of fostering resilience as part of effective organizational change management strategies.